Executive Compensation and Risk Taking - Bolton, Patrick; Mehran, Hamid; Shapiro, Joel (Review of Finance, 2015)
Abstract This article studies the connection between risk taking and executive compensation in financial institutions. A model of shareholders, debtholders, depositors, and an executive demonstrates that (i) excess risk taking can be addressed by basing compensation on both stock price and the credit default swaps (CDS) spread, (ii) shareholders may not be able to commit to design such contracts, and (iii) they may not want to due to distortions from deposit insurance or unobservable tail risk. The advantage of using the CDS spread rather than deferred compensation or debt is due to the fact that it is a market price and reduces agency costs.